Pengaruh E-Commerce dan Sistem Informasi Akuntansi Terhadap Kinerja UMKM Sektor Kuliner di Kota Medan - Elva Elva; Linda Wahyu Marpaung; Albert Herlambang (Politeknik Ganesha Medan, 2026)
The rapid advancement of information technology has transformed the way businesses interact with markets and consumers, particularly in the culinary sector of micro, small, and medium enterprises (MSMEs) in Medan City. Digitalization through e-commerce provides opportunities for MSMEs to expand market reach, reduce operational costs, and improve transaction efficiency. Meanwhile, the implementation of accounting information systems (AIS) plays a crucial role in enhancing the accuracy of financial records, transparency of reporting, and supporting managerial decision-making. This study aims to analyze the influence of e-commerce and AIS on the performance of culinary MSMEs in Medan. A quantitative approach with causal analysis was employed, involving 223 respondents selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed with multiple linear regression using SPSS version 25. The findings reveal that both e-commerce and AIS have a positive and significant effect on MSME performance, both partially and simultaneously. The coefficient of determination (R²) of 49.8% indicates that nearly half of the variation in MSME performance can be explained by these two variables, while the remaining 50.2% is influenced by other factors not examined in this study. The results conclude that the synergy between e-commerce adoption and AIS implementation is a critical strategy for improving competitiveness, operational efficiency, and customer satisfaction in the digital era. Practical implications highlight the need for strengthening digital and accounting literacy among MSME actors, supported by government policies to enhance access to technology. Future research is recommended to include additional variables such as entrepreneurial orientation, product innovation, or the role of social media to provide a more comprehensive understanding of factors affecting MSME performance in the digital economy.